Biallelic CACNA2D2 variants in epileptic encephalopathy and cerebellar atrophy. Issue 8 (11th July 2019) - Punetha, Jaya; Karaca, Ender; Gezdirici, Alper; Lamont, Ryan E.; Pehlivan, Davut; Marafi, Dana; Appendino, Juan P.; Hunter, Jill V.; Akdemir, Zeynep C.; Fatih, Jawid M.; Jhangiani, Shalini N.; Gibbs, Richard A.; et al.
Abstract: Objective: To characterize the molecular and clinical phenotypic basis of developmental and epileptic encephalopathies caused by rare biallelic variants in CACNA2D2 . Methods: Two affected individuals from a family with clinical features of early onset epileptic encephalopathy were recruited for exome sequencing at the Centers for Mendelian Genomics to identify their molecular diagnosis. GeneMatcher facilitated identification of a second family with a shared candidate disease gene identified through clinical gene panel‐based testing. Results: Rare biallelic CACNA2D2 variants have been previously reported in three families with developmental and epileptic encephalopathy, and one family with congenital ataxia. We identified three individuals in two unrelated families with novel homozygous rare variants in CACNA2D2 with clinical features of developmental and epileptic encephalopathy and cerebellar atrophy. Family 1 includes two affected siblings with a likely damaging homozygous rare missense variant c.1778G>C; p.(Arg593Pro) in CACNA2D2 . Family 2 includes a proband with a homozygous rare nonsense variant c.485_486del; p.(Tyr162Ter) in CACNA2D2 . We compared clinical and molecular findings from all nine individuals reported to date and note that cerebellar atrophy is shared among all. Interpretation: Our study supports the candidacy of CACNA2D2 as a disease gene associated with a phenotypic spectrum of neurological disease that include features of developmental and epileptic encephalopathy, ataxia, and cerebellar atrophy. Age at presentation may affect apparent penetrance of neurogenetic trait manifestations and of a particular clinical neurological endophenotype, for example, seizures or ataxia.